Prediction of striatal D2 receptor binding by DRD2/ANKK1 TaqIA allele status. Issue 10 (17th June 2016) - Eisenstein, Sarah A.; Bogdan, Ryan; Love‐Gregory, Latisha; Corral‐Frías, Nadia S.; Koller, Jonathan M.; Black, Kevin J.; Moerlein, Stephen M.; Perlmutter, Joel S.; Barch, Deanna M.; Hershey, Tamara
Abstract: In humans, the A1 (T) allele of the dopamine (DA) D2 receptor/ankyrin repeat and kinase domain containing 1 ( DRD2/ANKK1 ) TaqIA (rs1800497) single nucleotide polymorphism has been associated with reduced striatal DA D2/D3 receptor (D2/D3R) availability. However, radioligands used to estimate D2/D3R are displaceable by endogenous DA and are nonselective for D2R, leaving the relationship between TaqIA genotype and D2R specific binding uncertain. Using the positron emission tomography (PET) radioligand, ( N ‐[ 11 C]methyl)benperidol ([ 11 C]NMB), which is highly selective for D2R over D3R and is not displaceable by endogenous DA, the current study examined whether DRD2/ANKK1 TaqIA genotype predicts D2R specific binding in two independent samples. Sample 1 ( n  = 39) was composed of obese and nonobese adults; sample 2 ( n  = 18) was composed of healthy controls, unmedicated individuals with schizophrenia, and siblings of individuals with schizophrenia. Across both samples, A1 allele carriers (A1+) had 5 to 12% less striatal D2R specific binding relative to individuals homozygous for the A2 allele (A1−), regardless of body mass index or diagnostic group. This reduction is comparable to previous PET studies of D2/D3R availability (10–14%). The pooled effect size for the difference in total striatal D2R binding between A1+ and A1− was large (0.84). In summary, in line with studies using displaceable D2/D3R radioligands, our results indicate that DRD2/ANKK1 TaqIA allele status predicts striatal D2R specific binding as measured by D2R‐selective [ 11 C]NMB. These findings support the hypothesis that DRD2/ANKK1 TaqIA allele status may modify D2R, perhaps conferring risk for certain disease states. Abstract : We investigated the difference in striatal dopamine D2 receptor binding, as measured by PET with ( N ‐[ 11 C]methyl)benperidol ([ 11 C]NMB), between A1 allele carriers (A1+) and individuals homozygous for the A2 allele (A1‐) of the DRD2/ANKK1 TaqIA single nucleotide polymorphism. In Study 1, A1+ had 5–12% less striatal [ 11 C]NMB binding than A1‐.